Manufacturing of Ceramic Based Mechatronic Integrated Devices Using Laser-Direct-Structuring - Bräuer, Philipp; Stoll, Thomas; Muckelbauer, Martin; Häußler, Felix; Hensel, Alexander; Franke, Jörg (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC), 2022)
This paper introduces a convenient way to manufacture ceramic based mechatronic integrated devices by means of laser-direct-structuring (LDS). The process to achieve that, consists of pretreatment, laser structuring, chemical metallization, and assembly. In the experiments, the alumina samples are blackened to enable the interaction with the laser beam. For the structuring process, a Nd:YAG laser with a wavelength of 1,064 nm and a maximum power of 17 W is used. The design of experiment (DoE) in the first place includes 54 different laser parameter settings. Subsequently the best parameter of the DoE with respect to surface roughness after laser structuring, chemical copper metallization thickness and surface roughness after chemical copper metallization is used to produce antenna samples. The surface roughness after laser structuring and after chemical copper metallization is aimed to be as low as possible to optimize the properties of the antennas. Parameters resulting from the DoE show a copper metallization layer thickness of 8.78 μm after 120 minutes of chemical metallization. These parameters are then used to manufacture microstrip and coplanar waveguide samples which are measured with a microscope to verify the dimension conformity with the test design. <br
Keywords: MID; Ceramics; Lasers; Mechatronics; Antennas